2006
DOI: 10.2337/db06-0188
|View full text |Cite
|
Sign up to set email alerts
|

Saturated, but Not Unsaturated, Fatty Acids Induce Apoptosis of Human Coronary Artery Endothelial Cells via Nuclear Factor-κB Activation

Abstract: High nonesterified fatty acid (NEFA) concentrations, as observed in the metabolic syndrome, trigger apoptosis of human umbilical vein endothelial cells. Since endothelial apoptosis may contribute to atherothrombosis, we studied the apoptotic susceptibility of human coronary artery endothelial cells (HCAECs) toward selected NEFAs and the underlying mechanisms. HCAECs were treated with single or combined NEFAs. Apoptosis was quantified by flow cytometry, nuclear factor B (NFB) activation by electrophoretic mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 33 publications
8
107
0
2
Order By: Relevance
“…Unsaturated FAs have been shown to inhibit the LPS-induced NF-κB signalling pathway in macrophages [25,34]. Moreover, monounsaturated FAs, such as oleate, protect against various lipotoxic effects of palmitate [35][36][37][38][39]. The protective effects of oleate are reported at concentrations lower or equimolar to that of palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…Unsaturated FAs have been shown to inhibit the LPS-induced NF-κB signalling pathway in macrophages [25,34]. Moreover, monounsaturated FAs, such as oleate, protect against various lipotoxic effects of palmitate [35][36][37][38][39]. The protective effects of oleate are reported at concentrations lower or equimolar to that of palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…[52] Palmitoleic acid supplementation seems to promote important effects to control obesity. For example, Yang et al [49] showed that palmitoleic acid induces satiety in mice, while studies with obese high-fat diet fed mice have shown that daily administration of palmitoleic acid (300 mg kg −1 ) for 10 d increased whole body insulin sensitivity [4,51] and enhanced glucose uptake into adipose tissue by modulation of GLUT-4 content and AMPK phosphorylation.…”
Section: Obesity and Dyslipidemiamentioning
confidence: 99%
“…Cell culture/animal model Effect of palmitoleic acid [8] Rat pancreatic cells exposed to glucose β Cell proliferation and function [9] Rat islets of Langerhans exposed to several glucose levels Counteracted effect of high glucose [7] Human islet cells exposed to several glucose levels β Cell proliferation; counteracted effect of high glucose [76] Rat L6 skeletal muscle cells Glucose uptake, glucose oxidation, glycogen synthesis not attributed to insulin, GLUT 1 and 4 [52] Endothelial cells treated with single or combined fatty acids Stearate-induced apoptosis [3] Mice deficient in adipose tissue lipid chaperones aP2 and mal1, showing a high production of palmitoleic acid in adipose tissue, fed on HFD Mouse resistant to the deleterious effects of high fat, AKT and IRS (muscle), insulin action (muscle), SCD-1, FAS, ELOV6 (liver), NAFLD [94] F1 hamster, 12 weeks diet with 10% (wt:wt) of macadamia, palm, coconut or sunflower oil (n = 8)…”
Section: Referencementioning
confidence: 99%
See 2 more Smart Citations